Navigating the Transition: How Homesickness Relates to Academic Stress in First-Year University Students - Valentina Putri Permatasari; Woro Apriliana Sari (Universitas Ahmad Dahlan, 2026)
The transition to higher education requires substantial adaptability, and inadequate adjustment may intensify homesickness among first-year migrant students. This cross-sectional correlational study examined the association between homesickness and academic stress among 310 first-year migrant students at Universitas Negeri Semarang (aged 18–20 years) recruited through purposive sampling. Data were collected using the Student-Life Stress Inventory and the Homesickness Questionnaire. Given non-normal score distributions, Spearman’s rho correlation was applied. Results indicated a significant, moderate positive association between homesickness and academic stress (rs = .479, p < .001). Thus, students reporting greater homesickness also reported higher perceived academic stress while living away from home. These findings underscore the need for universities to provide early screening and targeted adjustment support e.g., orientation-based transition assistance and psychoeducational programs to help migrant students manage emotional transitions and mitigate academic stress.